THE ROLE OF INTERNET IN MODERN EDUCATION - Nurmurodova, Shahlo Sobir qizi; Burkhanova, Mamura Gulyamovna (Innovative Development in Educational Activities, 2022)
The part of web part in cutting edge education Internet, the foremost valuable innovation of present day times which makes a difference us not as it were in our everyday lives but too in proficient lives. For instructive purposes, it is broadly utilized to assemble data and to do investigate or include to the information of different subjects.